Penyuluhan Dan Pelatihan Keamanan Data Digital Bagi Masyarakat Dari Ancaman Kejahatan Cyber - Rafly Fandiansyah; Mirza Cahya Ningrum; Caroline Julyana Magdalena; Muhammad Gymnastiar; Naufal Eka Wicaksono; Naufal Arif Fadilah; Raka Rismayana; Muhammad Reinaldy Santoso; Putra Aldi Purnama; Pahrizal Pahrizal; Nurcholis Nurcholis; Herlawati (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
The rapid development of information technology has led to increased use of digital media by the community, which has not been accompanied by adequate understanding of digital data security. This condition makes the community vulnerable to various cybercrime threats such as online fraud, personal data theft, phishing, and the spread of hoaxes. This community service activity aims to improve the digital literacy and awareness of residents of Taman Kebayoran Housing Area RW 013, Setiamekar Village, Bekasi Regency, regarding the importance of digital data security through counseling and training programs. The implementation methods include initial socialization, face to face counseling, digital data security training, and the development of a Housing Profile Website as an official and verified information medium. The results show an increase in community understanding of types of cyber threats, methods to identify false information, and preventive measures against digital fraud. In addition, the existence of the housing profile website is considered effective in supporting information transparency and strengthening communication between community administrators and residents. The originality of this activity lies in the integration of community based cybersecurity education with the development of a local digital platform that functions as a literacy and official information medium. This program is expected to serve as a sustainable community service model in building a safe and responsible digital ecosystem at the neighborhood level.